Empirical Analysis of Factors Influencing High School Students' Career Decision Making - Ananda Dea Saputri; Ayong Lianawati; Tri Rahmawati; Muhammad Iqbal Harits Amrulloh; Dwi Wulansari (Ma'soem University, 2026)
This study aims to analyze the influence of environmental factors, interests and talents, learning experiences, and personality on students' career decision-making. The study used a quantitative approach, employing a survey method, with 206 grade XI students of SMA Negeri 15 Surabaya selected through purposive sampling. Data were collected using a questionnaire that had met the validity and reliability tests (? = 0.90). Data analysis used multiple linear regression. The results showed that environmental factors, interests and talents, learning experiences, and personality had a significant influence on students' career decision-making (p < 0.05), both in partial and simultaneous analyses (F = 1203.884). Environmental factors were the most dominant variable (? = 0.613), followed by personality (? = 0.464), learning experiences (? = 0.268), and interests and talents (? = 0.185). The coefficient of determination (R²) value of 0.960 indicated that 96.0% of the variation in career decision-making could be explained by these four factors.